2020
DOI: 10.1002/rrq.314
|View full text |Cite
|
Sign up to set email alerts
|

Of Research Reviews and Practice Guides: Translating Rapidly Growing Research on Adolescent Literacy Into Updated Practice Recommendations

Abstract: The demand for evidence‐based instructional practices has driven a large supply of research on adolescent literacy. Documenting this supply, Baye, Inns, Lake, and Slavin’s 2019 article in Reading Research Quarterly synthesized far more studies, with far more rigorous methodology, than had ever been collected before. What does this mean for practice? Inspired by this article, I investigated how this synthesis compared with the 2008 U.S. Institute of Education Sciences practice guide for adolescent literacy. I a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Of particular relevance to the present study, they further found that the cross-cutting factors of extra daily courses for reading (i.e., RICs) and the use of technology did not have significant effects on students' reading achievement. In light of insights afforded by this and other quantitative syntheses, Reynolds (2020) recently called for an update to existing adolescent literacy practice guidelines (i.e., Kamil et al, 2008). He argued that a revision must reflect a conceptually inclusive definition of adolescent literacy and incorporate findings from more recent research, including qualitative research.…”
Section: The Sociopolitical Context Of Adolescent Literacy Interventions In the 21st Centurymentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular relevance to the present study, they further found that the cross-cutting factors of extra daily courses for reading (i.e., RICs) and the use of technology did not have significant effects on students' reading achievement. In light of insights afforded by this and other quantitative syntheses, Reynolds (2020) recently called for an update to existing adolescent literacy practice guidelines (i.e., Kamil et al, 2008). He argued that a revision must reflect a conceptually inclusive definition of adolescent literacy and incorporate findings from more recent research, including qualitative research.…”
Section: The Sociopolitical Context Of Adolescent Literacy Interventions In the 21st Centurymentioning
confidence: 99%
“…Previous findings from the reviews cited above provide valuable insights and recommendations about specific programs and practices that can assist researchers, policymakers, and practitioners as they consider how to best support adolescents' literacy learning. Yet, there are also limitations and potential consequences of basing recommendations solely on quantifiable outcome measures (Almasi et al, 2006;Greenleaf & Petrosino, 2009;Reynolds, 2020). Relying exclusively on such measures overlooks other information about literacy teaching and learning (e.g., students' experiences and perspectives) that should be included in determinations about what constitutes effectiveness (de los Ríos & Seltzer, 2017;Franzak, 2006;Muhammad & Haddix, 2016;Vasudevan & Campano, 2009).…”
Section: The Sociopolitical Context Of Adolescent Literacy Interventions In the 21st Centurymentioning
confidence: 99%
“…Finally, the Guide was also limited by the research available to the authors in 2008. Elsewhere, I show that the Guide deemed 34 studies as “rigorous” evidence (see Reynolds, 2020 for a fuller investigation of the methodology and the findings explained in this paragraph). To determine the relevance of the Guide’s recommendations for grades 4–12 students today, I tracked down those 34 studies.…”
Section: The 2008 Practice Guide (And Its Limitations)mentioning
confidence: 99%
“…Therefore, educators who rely heavily on that Guide may be missing important opportunities to improve instruction. While my earlier report (Reynolds, 2020) more thoroughly documented the limitations of the Guide, this article presents instructional examples of how educators can incorporate new findings into their instruction, and focuses on how organizations like the International Literacy Association (ILA) and National Council of Teachers of English (NCTE) can leverage their expertise to deliver regular advice to educators.…”
Section: The 2008 Practice Guide (And Its Limitations)mentioning
confidence: 99%
See 1 more Smart Citation